Comparison of Existence Concept in the Works of Jean-Paul Sartre and Hemingway with Emphasis on the Educational Views of Existentialism - Saeid Rahimipour (Comparative Education Society of Iran ( CESIR), 2021)
The French philosopher Jean-Paul Sartre may have inadvertently bridged the gap between the philosophy of literature and education to show Existentialism does not follow the insipid method of other philosophical schools in presenting its basic ideas and concepts. The social consequences of World War II and the expectations of the young generation after the war in Europe also paved the way for the entry of the philosophical views of existentialist philosophers into literature and education. On the other hand, authors became interested in philosophical topics and subconsciously incorporated them into their stories. In the meantime, the educational implications of existentialist ideas drew the attention of educational philosophers to both the fields of philosophy and literature. Accordingly, the aim of the present researcher is to study and compare the concept of existence in the works of the French philosopher Jean-Paul Sartre and the American writer Ernest Hemingway with emphasis on the educational views of the school of existentialism. The method of the present study is a qualitatively comparative with the philosophical approach. The research population includes all the works of two selected authors along with books, articles and related works. The research sample was purposefully selected and the data analysis method is thematic content analysis. The research findings show that there are similarities between Sartre and Hemingway's works in terms of attention to issues such as the concept of existence, choice and responsibility, human freedom, and mental illnesses like anxiety and depression. The findings also show that from an educational perspective, Sartre's view is based on pessimism and Hemingway's view is based on optimism.